UHPLC-MS/MS-BASED PLASMA LIPIDOMICS REVEAL ALTERATIONS ASSOCIATED WITH EXCLUSIVE ENTERAL NUTRITION TREATMENT IN ADULT PATIENTS WITH ACTIVE CROHN'S DISEASE. (22nd January 2022) - Yang, Qingfan; Huang, ZiCheng; Liu, Hailing; Chao, Kang; Gao, Xiang
Abstract: BACKGROUND: Exclusive enteral nutrition (EEN) is an effective treatment for active Crohn's disease (CD), although the mechanisms is unclear. Lipid metabolism and signaling have been suggested to play an important role in the pathophysiology of the disease, but their relationship with EEN therapy has not been reported. Hence, we assessed plasma lipid profiles of adult patients with active CD before and after EEN and compared them to those of healthy controls. METHODS: Adult patients with active CD (n=11) who received EEN with an amino acid-based enteral nutrition formula for 12 weeks and age- and sex-matched healthy controls (n=17) were recruited. Plasma lipid profiles of 869 lipid species were measured before and after EEN in both groups using ultrahigh performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS). The CD activity index (CDAI), high-sensitivity C-reactive protein (hs-CRP) level, and nutrition-associated indices were evaluated. CDAI <150 and a Simple Endoscopic Score for CD (SES-CD) ≤2 indicated clinical remission and mucosal healing (MH), respectively. RESULTS: After 12 weeks of EEN, 81.8% (9 of 11) patients achieved remission with a significant decrease in the CDAI (P<0.001) and hs-CRP levels (P<0.001). Ten patients had a SES-CD score of >2 before EEN, which declined after EEN (P=0.009), with four patients achieving MH. Before EEN initiation, 80 lipid species/17 lipid classes were significantly different between patients with CD and healthy controls. After EEN initiation, 103 lipid species/11 lipid classes were significantly different between patients with CD and healthy controls. Thirty-eight significantly different lipid species from eight lipid classes—cholesterolester (n=1), lysophosphatidylcholine (n=3), monogalactosyldiacylglycerol (n=1), phosphatidylcholine (n=18), phosphatidylethanolamine (n=3), phosphatidylinositol (n=4), phosphatidylserine (n=1), and phosphatidylglycerol (n=7)—were identified in patients with CD before and after EEN. Among these lipid classes, the levels of monogalactosyldiacylglycerol, phosphatidylinositol, and phosphatidylcholine decrased significantly and that of phosphatidylglycerol increased significantly before EEN in patients with CD compared to those in healthy controls (P<0.05). These lipids returned to similar levels of healthy controls after EEN (P>0.05). Lipid classes and species were significantly associated with clinical indices of CDAI, hs-CRP, and MH. Pathway analysis suggested that arachidonic acid, glycerophospholipid, linoleate, and phosphatidylinositol phosphate metabolisms were related to the mechanism of EEN treatment. CONCLUSION: EEN leads to the alterations in multiple lipid classes and species, in keeping with improvement in clinical response. However, further studies are needed to confirm their precise roles.